The Differences in Attitudes about Their Society between 14 Years Old Pupils with and without an Immigration Background: A Cross-National Comparison - PROKIC, Tijana; DRONKERS, Jaap (Journal of Research in Educational Sciences; Vol 1 No 1 (2010): JRES, Volume I, Issue 1(1), Summer 2010, 2010)
In this paper we analyze the attitudes of 14 year old children of first and second generation immigrants and their civic attitudes about (aspects of) the society of destination. We use data from the Civic Education Study conducted by International Educational Association (IAE) in 1999. This Civic Education Study tests civic knowledge, civic attitudes and civic participation of 14 year old students. We have five dependent variables in 11 countries: trust in government related institution positive attitudes towards immigrants, positive attitudes towards one’s nation of residence positive attitudes towards women’s rights and civic participation. 14-year pupils with an immigrant background had stronger positive attitudes towards immigrants, stronger negative attitudes towards women’s political and economic rights, stronger negative attitudes towards the nation of residence and less outspoken lower trust in government related institutions. Second generation pupils do not deviate less than first generation, neither pupils in more inclusive societies differ less.